2004
DOI: 10.1084/jem.20041277
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of an endogenous chemotactic ligand specific for FPRL2

Abstract: Chemotaxis of dendritic cells (DCs) and monocytes is a key step in the initiation of an adequate immune response. Formyl peptide receptor (FPR) and FPR-like receptor (FPRL)1, two G protein–coupled receptors belonging to the FPR family, play an essential role in host defense mechanisms against bacterial infection and in the regulation of inflammatory reactions. FPRL2, the third member of this structural family of chemoattractant receptors, is characterized by its specific expression on monocytes and DCs. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 47 publications
(74 reference statements)
8
113
1
Order By: Relevance
“…8B, treatment of MoDCs with Hp(2-20) (50 M) plus LPS (100 ng/ml) inhibited IL-12 production by DCs, suggesting that LPS-induced MoDC maturation is inhibited by Hp(2-20) treatment, and that the activation of FPRL2 by Hp(2-20) inhibits LPS-induced MoDC maturation. More recently, the FPRL2-selective peptide ligand, F2L, was reported to be a natural DC chemoattractant (20). We also found that treatment with F2L (100 nM) plus LPS (100 ng/ml) significantly inhibited IL-12 production by LPS (Fig.…”
Section: Both Fpr and Fprl2 Are Involved In The Wkymvm-induced Inhibisupporting
confidence: 64%
See 1 more Smart Citation
“…8B, treatment of MoDCs with Hp(2-20) (50 M) plus LPS (100 ng/ml) inhibited IL-12 production by DCs, suggesting that LPS-induced MoDC maturation is inhibited by Hp(2-20) treatment, and that the activation of FPRL2 by Hp(2-20) inhibits LPS-induced MoDC maturation. More recently, the FPRL2-selective peptide ligand, F2L, was reported to be a natural DC chemoattractant (20). We also found that treatment with F2L (100 nM) plus LPS (100 ng/ml) significantly inhibited IL-12 production by LPS (Fig.…”
Section: Both Fpr and Fprl2 Are Involved In The Wkymvm-induced Inhibisupporting
confidence: 64%
“…(19) was a gift from Dr. K. S. Hahm (Chosun University, Gwangju, Korea). Acetylated F2L (Ac-MLGMIKNS LFGSVETWPWQVL) (20) was synthesized by Anygen. PE-conjugated mAb against CD86, FITC-conjugated mAb against HLA-DR, and human recombinant TNF-␣ were from BD Pharmingen.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…The first ligand shown to bind with high affinity (low nanomolar range) to this receptor was lipoxin A4 (LXA4), an anti-inflammatory lipid mediator [10]. Recently, FPRL1 has emerged as a promiscuous receptor, also activated by the pathogenderived peptide Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) from Helicobacter pylori, by host-derived proteins and peptides such as Ac1-25 from annexin 1, cathelicidin LL37, a fragment of the urokinase receptor, the serum amyloid A, the amyloid b peptide (Ab42), the prion protein fragment PrP(106-126), the neuroprotective peptide humanin, and by different synthetic peptides including the hexapeptide Trp-LysTyr-Met-Val-D-Met-NH 2 (WKYMVm) [11,12]. FPRL2 does not respond to fMLF [13], but instead is activated by some non-formylated chemotactic peptides identified as agonists for FPRL1 [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…FPRL2 does not respond to fMLF [13], but instead is activated by some non-formylated chemotactic peptides identified as agonists for FPRL1 [14,15]. Recently, an acetylated Nterminal peptide derived from the human heme-binding protein has been identified as a ligand specific for FPRL2 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is known that apoptotic cells release chemotactic factors to attract phagocytes. F2L act as a chemoattractant for monocytes, and dendritic cells that would induce cellular responses against apoptotic cells [14]. Interestingly, we also found that F2L induced the chemotactic migration of endothelial cells, indicat- After an 18 h incubation period, we assessed the tube formation by obtaining photographs from an inverted phase contrast microscope image (50·) (A).…”
Section: Discussionmentioning
confidence: 73%